Therapeutic Potential of STE20-Type Kinase STK25 Inhibition for the Prevention and Treatment of Metabolically Induced Hepatocellular CarcinomaSummary - Ying Xia; Mara Caputo; Emma Andersson; Bernice Asiedu; Jingjing Zhang; Wei Hou; Manoj Amrutkar; Emmelie Cansby; Nadia Gul; Anne Gemmink; Caitlyn Myers; Mariam Aghajan; et al. (Cellular and Molecular Gastroenterology and Hepatology)
Background & Aims: Hepatocellular carcinoma (HCC) is a rapidly growing malignancy with high mortality. Recently, metabolic dysfunction-associated steatohepatitis (MASH) has emerged as a major HCC catalyst; however, signals driving transition of MASH to HCC remain elusive and treatment options are limited. Herein, we investigated the role of STE20-type kinase STK25, a critical regulator of hepatocellular lipotoxic milieu and MASH susceptibility, in the initiation and progression of MASH-related HCC. Methods: The clinical relevance of STK25 in HCC was assessed in publicly available datasets and by RT-qPCR and proximity ligation assay in a validation cohort. The functional significance of STK25 silencing in human hepatoma cells was evaluated in vitro and in a subcutaneous xenograft mouse model. The therapeutic potential of STK25 antagonism was examined in a mouse model of MASH-driven HCC, induced by a single diethylnitrosamine injection combined with a high-fat diet. Results: Analysis of public databases and in-house cohorts revealed that STK25 expression in human liver biopsies positively correlated with HCC incidence and severity. The in vitro silencing of STK25 in human hepatoma cells suppressed proliferation, migration, and invasion with efficacy comparable to that achieved by anti-HCC drugs sorafenib or regorafenib. STK25 knockout in human hepatoma cells also blocked tumor formation and growth in a subcutaneous xenograft mouse model. Furthermore, pharmacologic inhibition of STK25 with antisense oligonucleotides—administered systemically or hepatocyte-specifically—efficiently mitigated the development and exacerbation of hepatocarcinogenesis in a mouse model of MASH-driven HCC. Conclusion: This study underscores STK25 antagonism as a promising therapeutic strategy for the prevention and treatment of HCC in the context of MASH.